Transmissibility of Livestock-associated Methicillin-Resistant Staphylococcus aureus - Hetem, David J. (Centers for Disease Control and Prevention, 2013)
Previous findings have suggested that the nosocomial transmission capacity of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is lower than that of other MRSA genotypes. We therefore performed a 6-month (June 1–November 30, 2011) nationwide study to quantify the single-admission reproduction number, R(A), for LA-MRSA in 62 hospitals in the Netherlands and to compare this transmission capacity to previous estimates. We used spa typing for genotyping. Quantification of R(A) was based on a mathematical model incorporating outbreak sizes, detection rates, and length of hospital stay. There were 141 index cases, 40 (28%) of which were LA-MRSA. Contact screening of 2,101 patients and 7,260 health care workers identified 18 outbreaks (2 LA-MRSA) and 47 secondary cases (3 LA-MRSA). R(A) values indicated that transmissibility of LA-MRSA is 4.4 times lower than that of other MRSA (not associated with livestock).